2020
DOI: 10.1038/s42003-020-01259-8
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus spp. attenuate antibiotic-induced immune and microbiota dysregulation in honey bees

Abstract: Widespread antibiotic usage in apiculture contributes substantially to the global dissemination of antimicrobial resistance and has the potential to negatively influence bacterial symbionts of honey bees (Apis mellifera). Here, we show that routine antibiotic administration with oxytetracycline selectively increased tetB (efflux pump resistance gene) abundance in the gut microbiota of adult workers while concurrently depleting several key symbionts known to regulate immune function and nutrient metabolism such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 79 publications
6
58
2
Order By: Relevance
“…Taken together, these results suggest that Lactobacillus, Bifidobacterium, and Gammaproteobacteria may be positively associated with exposure to agrochemicals. Notably, our results differ from a study on European honey bees that reported decreases in several Lactobacillius ASVs following exposure to oxytetracycline (Daisley et al, 2020).…”
Section: Core Microbial Taxa and Tetracycline Treatmentcontrasting
confidence: 99%
“…Taken together, these results suggest that Lactobacillus, Bifidobacterium, and Gammaproteobacteria may be positively associated with exposure to agrochemicals. Notably, our results differ from a study on European honey bees that reported decreases in several Lactobacillius ASVs following exposure to oxytetracycline (Daisley et al, 2020).…”
Section: Core Microbial Taxa and Tetracycline Treatmentcontrasting
confidence: 99%
“…and Gilliamella spp., can survive and proliferate thanks to tet determinants. Recently, Daisley et al (40) found that the routine administration of oxytetracycline increases tetB and tetY abundance in the gut microbiota of adult workers associated with a depletion of the major symbiont taxa. The present study therefore confirms that honeybees represent an impressive reservoir of tetracycline resistance genes, even after two decades without antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics can influence the host by altering the species of gut microbiota. Daisley et al [ 119 ] documented the deleterious effects of antibiotics on the gut microbiome, immunity, and productivity of honeybees. Several residues of antibiotics and veterinary chemotherapeutics are detected in honey, showing that honeybees are still exposed to them, despite many countries banning their usage in beekeeping [ 120 , 121 ].…”
Section: Honeybee Microbiotamentioning
confidence: 99%